EFFECT OF RASKIN RICE INCOME AND PRICE ON RASKIN RICE CONSUMPTION LEVEL IN SIMPANG KIRI SUB-DISTRICT SUBULUSSALAM CITY - Endrian Syahlubis; Khairil Anwar (LPPM Universitas Malikussaleh, 2018)
The purpose of this study is to see the influence of the income and the price of raskin rice to the level of consumption of the community of the Subulussalam. The data is obtainedfrom 100 respondents. The method of analysis used in research is quantitative research. The result show thatthe price of raskin riceaffects the level of public consumption in Simpang Kiri district.